Calculation-experimental modeling of wear of cylindrical sliding bearings - Dykha, Aleksandr; Sorokatyi, Ruslan; Makovkin, Oleg; Babak, Oleg (Eastern-European Journal of Enterprise Technologies, 2017)
The problem of developing a calculation-experimental method for calculating wear of a sliding bearing based on a two-factor wear model (contact pressure - sliding velocity) with identification of wear resistance parameters was considered. Analysis of known studies has shown that existing approaches required solution of complex systems of integral-differential equations or cumbersome numerical methods that are unacceptable in the engineering practice. As a result, a model of the sliding bearing wear in conditions of boundary friction was obtained in a form of dependence of the wear rate on the dimensionless complexes of contact pressure and sliding velocity. On the basis of the proposed wear model, the wear-contact problem for a cylindrical sliding bearing was solved. The equation of equilibrium for medium pressures and the approximating function of linear wear from the arc of contact between the shaft and the bushing were used as the determining equations. The solution was obtained in a closed form as a dependence of wear degree on the friction path. To identify parameters of wear resistance in the wear model, a calculation-experimental method for determining calculated dependences of wear resistance parameters was developed on the basis of the wear test by the «cone – three balls» scheme. The results of wear tests of bronze conical specimens with a variable wear spot and two values of sliding velocity were taken as a base. An example of implementation of the calculation-experimental method for calculating wear of a cylindrical bearing was given. It has shown that the calculated wear values were consistent with the operational data on wear of sliding bearings. Influence of determining factors of sliding velocity and load on bearing wear was studied. The obtained results were recommended for predicting wear of sliding bearings at the design stage and optimizing their design and operational parameters